2017
DOI: 10.1089/omi.2017.0145
|View full text |Cite
|
Sign up to set email alerts
|

Public Health Burden of Hearing Impairment and the Promise of Genomics and Environmental Research: A Case Study in Ghana, Africa

Abstract: Hearing impairment (HI) is one of the most disabling conditions of major global health burden that contributes adversely to the social and economic development of a country, if not managed properly. A proper assessment of the nationwide burden and etiology of HI is instrumental in the prevention, treatment, and management of the condition. This article sought to perform an expert review of HI in Ghana to determine the present knowledge of its burden and possible causes of the condition. A literature search was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 46 publications
3
9
0
Order By: Relevance
“…Of interest, previous studies have shown that a common founder mutation accounted for about 16.2% of congenital HI was p.R143W in a random sample of Ghanaians affected by hearing loss (Hamelmann et al, 2001). To our knowledge, the contribution of connexin 30 to HI, and the carrier frequency of the GJB2 mutation in non-affected individuals has not been studied in Ghana (Adadey et al, 2017). In the present research, we aimed to investigate the putative environmental causes of childhood HI, and revisit the contribution of GJB2 , and to investigate GJB6 mutations in carefully selected samples of families segregating HI, and in isolated cases of putative genetic origin, as well control populations non-affected by HI, in Ghana.…”
Section: Introductionmentioning
confidence: 99%
“…Of interest, previous studies have shown that a common founder mutation accounted for about 16.2% of congenital HI was p.R143W in a random sample of Ghanaians affected by hearing loss (Hamelmann et al, 2001). To our knowledge, the contribution of connexin 30 to HI, and the carrier frequency of the GJB2 mutation in non-affected individuals has not been studied in Ghana (Adadey et al, 2017). In the present research, we aimed to investigate the putative environmental causes of childhood HI, and revisit the contribution of GJB2 , and to investigate GJB6 mutations in carefully selected samples of families segregating HI, and in isolated cases of putative genetic origin, as well control populations non-affected by HI, in Ghana.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve this symbiosis, an enormous commitment should be made by researchers, physicians, and the pharmaceutical industry, to conduct high-quality clinical trials that will benefit patients at the same time as we gain substantial scientific knowledge. 37 , 38 …”
Section: The Importance Of Precision Medicine In Countries With Limitmentioning
confidence: 99%
“…Two new (compared to the SCDO) upper classes have been included, namely: 'Disease Attribute' and 'Modifier' (see Figure 2). The 'Disease Attribute' class (see Figure 5) incorporates content similar to the SCDO's 'Association' class but notably also includes a 'Disease Cause' sub-class, which was found necessary due to the varied and often complex causes of hearing impairments [19][20][21][22]. The 'Disease Cause' class contains the term 'Unknown Etiology' and the two subclasses 'Environmental Disease Cause' and 'Intrinsic Disease Cause' [23][24][25], which are populated comprehensively with factors that cause or contribute in some way to HI.…”
Section: Hio General Descriptionmentioning
confidence: 99%